2021
DOI: 10.13057/biodiv/d220246
|View full text |Cite
|
Sign up to set email alerts
|

Composition and diversity of bacteria from giant Asian honeybee Apis dorsata gut

Abstract: Abstract. Niode NJ, Adji A, Rimbing J, Tulung M, Tallei TE. 2021. Composition and diversity of bacteria from giant Asian honeybee Apis dorsata gut. Biodiversitas 22: 906-912. As a social insect, honeybee possesses a unique gut bacteria community. Therefore, we need to understand the composition and diversity of bacteria in Apis dorsata gut, the largest honeybee species that live in the forest, especially in Southeast Asia. The present study aimed to investigate the gut bacteria of A. dorsata using a metabarcod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Previous studies showed that geographical location and even developmental stages can influence the diversity in composition of honeybee gut microbiota [ 35 , 36 , 37 ]. Among other factors, exposure to synthetic chemicals such as pesticides also determine the type of microbiota inhabiting honeybee gut [ 38 ]. Owing to distinct geographical and environmental conditions at the habitat of the host giant honeybee A. dorsata , some or all of these factors could have contributed to the occurrence of this novel Apilactobacillus species.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that geographical location and even developmental stages can influence the diversity in composition of honeybee gut microbiota [ 35 , 36 , 37 ]. Among other factors, exposure to synthetic chemicals such as pesticides also determine the type of microbiota inhabiting honeybee gut [ 38 ]. Owing to distinct geographical and environmental conditions at the habitat of the host giant honeybee A. dorsata , some or all of these factors could have contributed to the occurrence of this novel Apilactobacillus species.…”
Section: Resultsmentioning
confidence: 99%
“…The effective N species is an estimation of the effective number of equally abundant species that would yield the same diversity as the observed sample [27,28]. Simpson's index (D) measures the probability that two individuals randomly selected from the sample belong to the same species [29]. To obtain the inverse of Simpson's index (D), the reciprocal of D is taken.…”
Section: Microbial Alpha Diversitymentioning
confidence: 99%
“…The field of genomics has significantly transformed our understanding of the biological and evolutionary aspects of various organisms, including ants. The mitochondrial genome has emerged as a valuable instrument for investigating evolutionary histories, comprehending population genetics, and exploring ecological interactions among the genomic components of particular interest [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%